2021
DOI: 10.3390/plants10030563
|View full text |Cite
|
Sign up to set email alerts
|

Wild Plants Used as Herbs and Spices in Italy: An Ethnobotanical Review

Abstract: Wild edible plants are an essential component of people’s diets in the Mediterranean basin. In Italy, ethnobotanical surveys have received increasing attention in the past two centuries, with some of these studies focusing on wild edible plants. In this regard, the literature in Italy lacks the coverage of some major issues focusing on plants used as herbs and spices. I searched national journals for articles on the use of wild food plants in Italy, published from 1963 to 2020. Aims of the present review were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 75 publications
(69 reference statements)
1
32
1
Order By: Relevance
“…In our study, the EI was 10.3% considering only native and alien wild food plants; it was slightly lower (10.2%) when only native flora was taken into account. These values are consistent with those of other Italian regions (range 5.4-11%) for seasonings only [48], or different areas of the Iberian Peninsula (range 5.05-29.01%) for all food and medicinal uses [49]. Recently, Gras et al [44] have reported that 6.62% of the total native flora in the Catalan linguistic area has a traditional food use.…”
Section: General Datasupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, the EI was 10.3% considering only native and alien wild food plants; it was slightly lower (10.2%) when only native flora was taken into account. These values are consistent with those of other Italian regions (range 5.4-11%) for seasonings only [48], or different areas of the Iberian Peninsula (range 5.05-29.01%) for all food and medicinal uses [49]. Recently, Gras et al [44] have reported that 6.62% of the total native flora in the Catalan linguistic area has a traditional food use.…”
Section: General Datasupporting
confidence: 83%
“…vesca, and S. nigra (23) (Supplementary Material S2). The number of taxa used as seasoning in our study (79) was much higher than that listed by Motti [48] for Tuscany itself (24) and for other regions such as Campania (23), Abruzzo, and Lombardy (22 each). Most of these plants belong to Lamiaceae, Amaryllidaceae, and Apiaceae.…”
Section: Preparation Forms and Detailed Usescontrasting
confidence: 53%
“…Root sap of Glycyrrhiza is utilized in wine production in the middle region of Turkey [21]. Decoction of root is used as a mild laxative in Italy [22] and juice from root and stem is used as a stimulant, astringent, and tonic in Nepal [23]. It is mixed with tea as the cure for sore throat in Egypt [11].…”
Section: Traditional Usesmentioning
confidence: 99%
“…Since historic times, spices and herbs have been used as food flavors, and their effects on human health are still being investigated to understand the roles of their chemical components [1,2]. Rosmarinus officinalis L. (also known as Salvia rosmarinus Schleid) and Lavandula angustifolia Mill.…”
Section: Introductionmentioning
confidence: 99%